An institutional perspective on consumers' environmental awareness and pro‐environmental behavioral intention: Evidence from 39 countries. (1st October 2020) - Yang, Morgan X.; Tang, Xuan; Cheung, Man Lai; Zhang, Ying
Abstract: We adopted an institutional approach to examine the relationship between environmental awareness and pro‐environmental behavioral intention at the individual level. We also compared the moderating effects of regulative, normative, and cognitive social institutions on this relationship. Based on survey data representing 42, 962 consumers from 39 nations, we found that consumers' environmental awareness promoted their pro‐environmental behavioral intention. Moreover, we found that normative social institutions negatively moderated the relationship between environmental awareness and pro‐environmental behavioral intention, whereas cognitive social institutions positively moderated this relationship. This paper concludes with a discussion of the implications of these empirical findings.